13th International Conference on Emergency Medicine Singapore 9-12 Jun 2010 - Chew Keng, Sheng (Pusat Pengajian Sains Perubatan, 2010)
To determine demographic data and survival for In - hospital cardiac arrests. To examine effects of age, sex, and initial cardiac rhythm on circadian variability in sudden cardiac death. Methods : A prospective observational study of adult patients in S.lndia from January to December 2009. Patients admitted with non-traumatic cause, undergoing cardiac arrest and attempted resuscitation were Included in study. Entry criteria, time intervals, nodal events and arrest factors related to resuscitation outcome were recorded. Single target endpoint was neurologically intact survival at hospital discharge. Results : One hundred ninety patients underwent cardiac resuscitation, with 69 (36.3%) surviving for 1 hour, 25 (5.1 %) survived to discharge. The 190 patients had the following bata: mean age 63.9 years; male 78.0%; witnessed arrest 25.6%; duty doctor cardiopulmonary resuscitation 32.1 %; initial rhythm ventricular fibrillation/ventricular tachycardia 86.9%. Overall, neurologically intact survival was 1.4% (99% confidence interval [CI) 0.8% to 2.4%) Three patients were lost to follow-up. A circadian variation in the occurrence of sudden cardiac death was demonstrated, with a tow occurrence rate between midnight and 6 AM and a 2.4-fold increase between the rate at 6 AM and the rate at noon. The same circadian pattern was noted among both men and women, among both patients aged 18 to 70 and those older than 70 years, and among patients with various initial cardiac arrest rhythms (ventricular tachycardia or fibrillation, asystole, and electromechanical dissociation). However, the outcome of resuscitation in these patients (le, the rate of successful resuscitation and the rate of survivaQ did not demonstrate circadian variation. Discussion : In-hospital sudden cardiac death demonstrated circadian variation, and this variability was observed regardless of the patient's age, sex, or initial cardiac arrest rhythm. The outcome of resuscitation did not show circadian variability. These results suggest a common pathophysiologic mechanism leading to sudden cardiac death.